Análisis social y estético de la batalla de la carreta desde un enfonque artístico plástico - Buenaño Echeverría, Carlota Adalgiza (2014)
On May 9, 1895 the important war -time known as the Battle of the wagon or the plains of Puerto Pilo , between the forces of the interim government of Vicente Lucio Salazar and liberal commanded by orense official Manuel Serrano Renda revolutionary remembered.